Study on the Impact of CDI Limiter and CDI Unlimiter Usage on Motorcycle Fuel Consumption and Exhaust Gas Emissions - Hermansyah, Dedi; Afdal, Afdal; Zulkarnain, Zulkarnain; Koto, Rahmat Desman (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2024)
The imperfections in the ignition system have a significant impact on the power, torque, fuel consumption, and exhaust emissions of the engine. The ignition system in motorcycles has evolved from platinum technology to CDI. Current CDI systems commonly restrict spark ignition at specific revolutions. This study employs experimental methods to compare the CDI Unlimiter BRT Powermax Dual Band with CDI Limiter on motorcycles, focusing on fuel consumption and exhaust emissions. The fuel consumption test results indicate that the CDI Unlimiter is more efficient compared to the CDI Limiter. There is a decrease in emissions (CO), but an increase in emissions (HC) is observed with the CDI Unlimiter. Recommendations for further research could focus on enhancing fuel efficiency without increasing HC emissions. This study has the potential to serve as a foundation for the development of more environmentally friendly motorcycles in the future. Ketidaksempurnaan sistem pengapian berdampak signifikan pada daya, torsi, konsumsi bahan bakar, dan emisi gas buang dari mesin. Sistem pengapian pada sepeda motor berkembang dari teknologi platina ke CDI. CDI yang digunakan saat ini umumnya membatasi percikan api pada putaran tertentu. Penelitian ini menggunakan metode eksperimen untuk membandingkan CDI Unlimiter BRT Powermax Dual Band dengan CDI Limiter pada sepeda motor, fokus pada konsumsi bahan bakar dan emisi gas buang. Hasil uji konsumsi bahan bakar menunjukkan bahwa CDI Unlimiter lebih efisien dibandingkan dengan CDI Limiter. Terdapat penurunan pada emisi (CO), namun terjadi peningkatan emisi (HC) pada CDI Unlimiter. Rekomendasi untuk penelitian lebih lanjut dapat berfokus pada bagaimana meningkatkan efisiensi bahan bakar tanpa meningkatkan emisi HC. Penelitian ini berpotensi menjadi dasar untuk pengembangan sepeda motor yang lebih ramah lingkungan di masa depan.